2020
DOI: 10.1002/chem.201905506
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Induced Cyclization of Heteroatom‐Functionalized Alkynes: Progress, Challenges and Perspectives

Abstract: Metal-induced cyclization of functionalized alkynes represents one of the most general approaches to prepare organic heterocycles. AlthoughR u II centers are well-established to promote alkyne to vinylidener earrangements and many Ru II -mediated alkyne cyclizations have been rationalized to be the resultso fp ost-vinylidene transformations, recent discoveries indicate that Ru II centers can serve as electrophiles and induce alkyne cyclizationsw ithoutv inylidene intermediacy. In this Minireview,a no verview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 63 publications
(104 reference statements)
0
30
0
Order By: Relevance
“…While the formation of M–allenylidene complexes from alkyl- and aryl-substituted propargylic alcohols and Fe­(II)/Ru­(II)/Os­(II) precursors is well-documented, we discovered that pyridyl-substituted propargylic alcohols could be activated via non-vinylidene pathways to give M–indolizine complexes (Scheme ). , More recently, we reported the formation of 2-methylpyridinium-functionalized metallafuran and M–quinolizinium complexes from the reactions between Ru­(II)/Os­(II) precursors and picolinyl-substituted propargylic alcohol HCCC­(OH)­(Ph)­(CH 2 (2-py)), in which the former complexes were derived from non-vinylidene pathways . Evidently, the presence and the nature of nucleophilic functionality on alkynes diversify the mode of Fe­(II)/Ru­(II)/Os­(II)–alkyne interactions, and it is essential to control the selectivity of these modes (vinylidene vs non-vinylidene pathways) for rational molecular and catalytic designs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the formation of M–allenylidene complexes from alkyl- and aryl-substituted propargylic alcohols and Fe­(II)/Ru­(II)/Os­(II) precursors is well-documented, we discovered that pyridyl-substituted propargylic alcohols could be activated via non-vinylidene pathways to give M–indolizine complexes (Scheme ). , More recently, we reported the formation of 2-methylpyridinium-functionalized metallafuran and M–quinolizinium complexes from the reactions between Ru­(II)/Os­(II) precursors and picolinyl-substituted propargylic alcohol HCCC­(OH)­(Ph)­(CH 2 (2-py)), in which the former complexes were derived from non-vinylidene pathways . Evidently, the presence and the nature of nucleophilic functionality on alkynes diversify the mode of Fe­(II)/Ru­(II)/Os­(II)–alkyne interactions, and it is essential to control the selectivity of these modes (vinylidene vs non-vinylidene pathways) for rational molecular and catalytic designs.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been investigating the reaction mechanisms between d 6 transition metal complexes and functional alkynes and reported the isolation of monocyclic or bicyclic metallafurans from the reactions between terminal ynone HCC­(C=O)­R and d 6 transition metal precursors including cis -[Ru­([14]­aneS4)­Cl 2 ], cis -[M­(bpy) 2 Cl 2 ], and cis -[M­(dppm) 2 Cl 2 ] (M = Ru and Os; [14]­aneS4 = 1,4,8,11-tetrathiacyclotetradecane; bpy = 2,2′-bipyridine; dppm = 1,1-bis­(diphenylphosphino)­methane). ,,, We herein report the isolation of indolizine-fused ruthenafuran and osmafuran complexes from the one-pot reactions between cis -[Ru II /Os II (dppm) 2 Cl 2 ] and dipicolinyl-substituted propargylic substrates HCCC­(OR)­(CH 2 (2-py)) 2 . Notably, these complexes not only represent an unprecedented class of metallafurans but also provide insights via their formation mechanism into Ru/Os-induced alkyne transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of alkynes by transition-metal complexes has recently gained increasing research interest in the field of organometallic chemistry [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Although the formation of metal–vinylidene species via alkyne–vinylidene rearrangement has been regarded as a key step in Ru(II)-induced alkyne transformations, a number of our synthetic studies revealed that Ru(II) can also activate alkynes via “non-vinylidene” pathways [ 31 , 32 ]. With the aim to gain control on the modes of alkyne activation, we initiated research activities on probing and isolating intermediates and products from the reactions between functionalized alkynes and a variety of Fe(II), Ru(II) and Os(II) complexes [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , …”
Section: Introductionmentioning
confidence: 99%
“…Although the formation of metal–vinylidene species via alkyne–vinylidene rearrangement has been regarded as a key step in Ru(II)-induced alkyne transformations, a number of our synthetic studies revealed that Ru(II) can also activate alkynes via “non-vinylidene” pathways [ 31 , 32 ]. With the aim to gain control on the modes of alkyne activation, we initiated research activities on probing and isolating intermediates and products from the reactions between functionalized alkynes and a variety of Fe(II), Ru(II) and Os(II) complexes [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In 2015, we reported the synthesis of metallafuran complexes in the form of [M(bpy) 2 (C^O)] + from the reactions between cis -[M(bpy) 2 Cl 2 ] (M = Ru, Os; bpy = 2,2′-bipyridine) and ynone HC≡C(C=O)Ph in MeOH ( Scheme 1 a; C^O represents an anionic bidentate [ C (OMe)CHC(Ph) O ] − chelate, coordinating atoms in italics) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkenes and alkynes, as abundant and versatile feedstocks employed in the synthesis of natural products, pharmaceutical molecules and agricultural chemicals, represent one of the most significant classes of unsaturated organic compounds. Owning to their easy availability and rich reactivity, numerous elegant examples have been successfully established for the construction of an array of functionalized and useful molecular scaffolds over the past several years . However, in contras t to the extensive explorations of electron‐biased alkenes or alkynes, the straightforward transformations of alkenes or alkynes without any electron‐withdrawing or electron‐donating functional groups generally receive less attention from chemists.…”
Section: Introductionmentioning
confidence: 99%